2020
DOI: 10.3390/molecules25092214
|View full text |Cite
|
Sign up to set email alerts
|

Quality Characteristics and Volatile Profile of Macarons Modified with Walnut Oilcake By-Product

Abstract: Walnut oilcake is a low-cost by-product of the edible oil industry but at the same time it is a valuable source of dietary fiber, natural antioxidants, and polyunsaturated fatty acids. In the context of health-friendly confectionary food products and to reduce the production cost, the aim of this study was to investigate the effect of walnut oilcake by-product on the quality characteristics and volatile profile of modified macarons. For this purpose, GC-MS and ITEX/GC-MS techniques were used to obtain the fatt… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
17
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
2

Relationship

3
6

Authors

Journals

citations
Cited by 23 publications
(17 citation statements)
references
References 49 publications
0
17
0
Order By: Relevance
“…This could be justified by the L. plantarum strain, which is claimed by the literature as having an exceptionally broad capacity in different phytochemicals’ metabolic conversion through enzymes such as reductases, decarboxylases, glycosyl hydrolases, or even phenolic acid esterases [ 20 ]. The production of weak organic acids such as lactic and acetic ones through fermentation with heterofermentative LAB is claimed by a large body of literature—[ 19 , 26 , 43 , 44 ], —and it is supported by a low pH value, caused by LAB acidification matrix through fermentation [ 43 ]. Generally, acetic and lactic acids are characterized by Nissen et al [ 14 ] as performance fermentation process indicators for every LAB inoculum being the main metabolites of heterofermentative lactobacilli with a positive impact on the sensorial quality and safety of the final fermented food.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This could be justified by the L. plantarum strain, which is claimed by the literature as having an exceptionally broad capacity in different phytochemicals’ metabolic conversion through enzymes such as reductases, decarboxylases, glycosyl hydrolases, or even phenolic acid esterases [ 20 ]. The production of weak organic acids such as lactic and acetic ones through fermentation with heterofermentative LAB is claimed by a large body of literature—[ 19 , 26 , 43 , 44 ], —and it is supported by a low pH value, caused by LAB acidification matrix through fermentation [ 43 ]. Generally, acetic and lactic acids are characterized by Nissen et al [ 14 ] as performance fermentation process indicators for every LAB inoculum being the main metabolites of heterofermentative lactobacilli with a positive impact on the sensorial quality and safety of the final fermented food.…”
Section: Discussionmentioning
confidence: 99%
“…Saturated fatty acids (SFA) were calculated based on the sum of C4:0-C24:0, monounsaturated fatty acids (MUFA) were calculated as the sum of C16:1-C22:1, and polyunsaturated fatty acids (PUFA) were calculated as the sum of C18:2, C18:3, and C20:4. Unsaturated fatty acids (UFA) were calculated as the sum of MUFA and PUFA [ 26 ].…”
Section: Methodsmentioning
confidence: 99%
“…Wheat flour (WF) type 550 was purchased from Auchan supermarket in Timisoara, Romania. Based on the literature studies [ 7 ] and our own experience on obtaining flour composites [ 16 , 17 , 18 , 19 ], three types of flour composites were obtained: WFL10 (10% lupin flour and 90% wheat flour); WFL20 (20% lupin flour and 80% wheat flour); and WFL30 (30% lupin flour and 70% wheat flour).…”
Section: Methodsmentioning
confidence: 99%
“…The addition strongly influences the amount of linoleic and caproic acid but not the aroma of macarons. However, the sensory analysis demonstrated that macarons with an addition of more than 10% were not appreciated, due to the increase in phenolic and volatile compounds that affect the taste [88]. Walnut oilcake can be introduced, at different levels 0-20%, as a supplement in cake formulations.…”
Section: Dessertsmentioning
confidence: 99%